2022
DOI: 10.1177/07067437221090088
|View full text |Cite
|
Sign up to set email alerts
|

En Réponse Au Projet De Loi 2 : Associations Entre Les Démarches Légales D’affirmation Du Genre et Deux Indicateurs De Bien-être Chez Des Personnes Trans et Non-Binaires Du Québec

Abstract: Mots-clés bien-être, détresse psychologique, satisfaction devie, transition légale, identité de genre, trans, non-binaire

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The idea of discontinuation, especially as covered in the media, has already started to limit access to services, while research shows that many TNBY still experience many delays and challenges to access gender-affirming care (Bauer et al, 2021). These restrictions run counter to current knowledge which has shown that access to legal (Cotton et al, 2022), social (Durwood et al, 2017;Russell et al, 2018), andmedical (Pullen Sansfaçon, Medico, et al, 2023;Sorbara et al, 2020;Turban et al, 2020) transitions and interventions to the improvement of youth mental health. The findings of this research add to the current knowledge by highlighting how providers have encountered discontinuation as a diverse phenomenon, and are present regardless of their approach to practice.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of discontinuation, especially as covered in the media, has already started to limit access to services, while research shows that many TNBY still experience many delays and challenges to access gender-affirming care (Bauer et al, 2021). These restrictions run counter to current knowledge which has shown that access to legal (Cotton et al, 2022), social (Durwood et al, 2017;Russell et al, 2018), andmedical (Pullen Sansfaçon, Medico, et al, 2023;Sorbara et al, 2020;Turban et al, 2020) transitions and interventions to the improvement of youth mental health. The findings of this research add to the current knowledge by highlighting how providers have encountered discontinuation as a diverse phenomenon, and are present regardless of their approach to practice.…”
Section: Discussionmentioning
confidence: 99%
“…Du point de vue légal, la transition correspond à la modification de la mention de sexe et/ou au changement de prénom sur l'acte de naissance. Si l'accès à la transition légale varie d'un pays à l'autre, des recherches montrent que de pouvoir utiliser un prénom usuel, et d'être respecté quant aux pronoms utilisés ont des impacts positifs sur la santé mentale des jeunes TNB (Cotton, Martin-Storey, Le Corff, Beauchesne Lévesque et Pullen Sansfaçon, 2022;Russell, Pollitt, Li et Grossman, 2018).…”
Section: Contexteunclassified